Incubation of Isolated Wheat Starch with Proteolytic or Lipolytic Enzymes and Different Extraction Media Reveals a Tight Interaction Between Puroindolines and Lipids at Its Granule Surface. Issue 3 (14th May 2014) - Pauly, Anneleen; Pareyt, Bram; De Brier, Niels; Delcour, Jan A.
ABSTRACT: Differences in hardness of wheat cultivars have been related to differences in interactions between the starch granule surface and the gluten protein matrix that are mediated by the proteins puroindoline (PIN) A and B. We examined whether or not PINs and (polar) lipids are associated at the starch granule surface, and, if so, how they interact with the starch granule surface itself. Starch was isolated from a soft wheat cultivar containing both wild‐type PINs and incubated with peptidases or lipases, or in extraction media (typically used for defatting). Protein, PIN, and lipid levels revealed that PINs and lipids are tightly associated together at the starch granule surface. Our results imply that PINs need lipids for binding to the granule surface but not vice versa.